Pengaruh Kepemimpinan dan Motivasi Kerja terhadap Kinerja Organisasi Melalui Kepuasan Kerja Di Laboratorium Lingkungan PT. Medialab Indonesia - Kusworo, Hery; Indratjahyo, Hary; Harri, Muhammad (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2026)
This study aims to analyze the influence of leadership and work motivation on organizational performance through job satisfaction as a mediating variable at PT Medialab Indonesia. The research employed a quantitative, non-experimental, and non-comparative approach. analyzed using path analysis to examine both direct and indirect relationships among variables. The population consisted of all permanent employees of PT Medialab Indonesia, selected through a census technique. The results show that leadership and work motivation have a positive and significant effect on organizational performance. Job satisfaction also has a positive and significant effect on performance and mediates the relationships between leadership and performance, as well as between work motivation and performance. These findings indicate that effective leadership and high work motivation not only have a direct impact on organizational performance but also influence it indirectly through increased job satisfaction. Therefore, PT Medialab Indonesia should focus its human resource development strategies on enhancing leadership quality and implementing sustainable motivation systems to optimize organizational performance.